Numerical Analysis of the Klein-Gordon Equations by Using the New Iteration Transform Method. (5th August 2021) - Zadeh, Ahmad Haji; Jacob, Kavikumar; Shah, Nehad Ali; Chung, Jae Dong
Abstract : This paper presents an analysis based on a mixture of the Laplace transform and the new iteration method to obtain new approximate results of the fractional-order Klein-Gordon equations in the Caputo-Fabrizio sense. So, a general system to investigate the approximate results of the fractional-order Klein-Gordon equations is obtained. This technique's effectiveness is demonstrated by comparing the actual results of the fractional-order equations suggested with the results achieved.